2019
DOI: 10.1038/s41598-018-37429-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of access to amodal representations of category-level conceptual information

Abstract: Categories describe semantic divisions between classes of objects and category-based models are widely used for investigation of the conceptual system. One critical issue in this endeavour is the isolation of conceptual from perceptual contributions to category-differences. An unambiguous way to address this confound is combining multiple input-modalities. To this end, we showed participants person/place stimuli using name and picture modalities. Using multivariate methods, we searched for category-sensitive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 48 publications
(32 reference statements)
3
28
0
Order By: Relevance
“…To address the question of whether PRC semantic effects were larger than in other ATL regions, RSA effects were extracted from each region between 200 and 400 ms. This particular time window was chosen due to prior research implicating this time frame (Bankson et al, 2018 ; Chan et al, 2011 ; Y. Chen et al, 2016 ; Clarke et al, 2015 , 2018 ; Kreiman et al, 2000 ; Leonardelli et al, 2019 ; Mollo et al, 2017 ; Rogers et al, 2019 ; Rupp et al, 2017 ; Schendan & Ganis, 2012 ; Schendan & Maher, 2009 ; Sudre et al, 2012 ) and to avoid circular inference. PRC semantic effects were significantly greater than all ATL sub-regions except the temporal pole ( Figure 3C ); fusiform (p = 0.0078, PRC greater in 8/8 participants), inferior temporal (p = 0.016, PRC greater in 7/8 participants), middle temporal (p = 0.0391, PRC greater in 6/8 participants) but not the temporal pole (p = 0.078, 6/7 participants).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To address the question of whether PRC semantic effects were larger than in other ATL regions, RSA effects were extracted from each region between 200 and 400 ms. This particular time window was chosen due to prior research implicating this time frame (Bankson et al, 2018 ; Chan et al, 2011 ; Y. Chen et al, 2016 ; Clarke et al, 2015 , 2018 ; Kreiman et al, 2000 ; Leonardelli et al, 2019 ; Mollo et al, 2017 ; Rogers et al, 2019 ; Rupp et al, 2017 ; Schendan & Ganis, 2012 ; Schendan & Maher, 2009 ; Sudre et al, 2012 ) and to avoid circular inference. PRC semantic effects were significantly greater than all ATL sub-regions except the temporal pole ( Figure 3C ); fusiform (p = 0.0078, PRC greater in 8/8 participants), inferior temporal (p = 0.016, PRC greater in 7/8 participants), middle temporal (p = 0.0391, PRC greater in 6/8 participants) but not the temporal pole (p = 0.078, 6/7 participants).…”
Section: Resultsmentioning
confidence: 99%
“…This research looked to build-upon previous studies relating semantic-feature similarity effects to neural similarity, that suggested the perirhinal cortex uniquely represented semantic item information (Bruffaerts et al, 2013 ; Clarke & Tyler, 2014 ; Kivisaari et al, 2019 ; Martin et al, 2018 ), but perhaps in cohort with the temporal pole (Martin et al, 2018 ). Further, EEG and MEG studies point to semantic-feature effects for individual items beyond around 200 ms (Bankson et al, 2018 ; Clarke et al, 2015 , 2018 ; Leonardelli et al, 2019 ; Mollo et al, 2017 ; Schendan & Maher, 2009 ; Sudre et al, 2012 ) but lacked detailed spatial specificity. It should be stressed that these studies, along with the current study, probe the semantics of objects at a basic-level (e.g., basketball, lawnmower) rather than a superordinate category level (e.g., tool), which may be associated with more posterior regions of the VVP (Bi et al, 2016 ; Connolly et al, 2012 ; Devereux et al, 2018 ; Konkle & Caramazza, 2013 ; Peelen & Downing, 2017 ; Tyler et al, 2013b ) at earlier points in time (Clarke et al, 2015 ; Mace et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations